Revenge Porn Sebagai Suatu Bentuk Tindak Pidana Kekerasan Seksual Berbasis Elektronik - Faizal, Muhammad Fadhla; Farhan, Muhammad; Luthfi, Al Farell Omar; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Revenge porn, or the distribution of intimate content without permission for the purpose of revenge, is a form of crime that is growing along with rapid technological advances. This phenomenon is not only a serious violation of privacy, but also falls into the category of technology-based sexual violence. In the context of Indonesian law, Revenge Porn is classified as a criminal act and is regulated in various legal instruments such as the Information and Electronic Transactions Law (UU ITE), the Sexual Violence Crime Law (TPKS Law), and the Criminal Code (UU TPKS). Criminal Code). However, the application of the law in this case still faces challenges, ranging from inconsistent legal interpretation to public prejudice which often harms victims. As a form of technology-induced sexual violence, revenge porn has far-reaching psychological, social and legal consequences. Victims often suffer deep trauma, loss of reputation, and ongoing social pressure. In addition, the distribution of content through digital platforms broadens its scope and further worsens the situation of victims. On the other hand, perpetrators take advantage of the anonymity afforded by technology to commit their crimes, making prosecution more difficult. This research aims to analyze Revenge Porn as a form of violent sexual crime using technology, its impact